Testosterone positively regulates functional responses and nitric oxide expression in the isolated human corpus cavernosum. (24th August 2020) - Gur, Serap; Alzweri, Laith; Yilmaz‐Oral, Didem; Kaya‐Sezginer, Ecem; Abdel‐Mageed, Asim B; Dick, Brian; Sikka, Suresh C.; Volkan Oztekin, Cetin; Hellstrom, Wayne J. G.
Abstract: Background: Testosterone (T) deficiency is associated with erectile dysfunction (ED). The relaxant response of T on the corporal smooth muscle through a non‐genomic pathway has been reported; however, the in vitro modulating effects of T on human corpus cavernosum (HCC) have not been studied. Objectives: To compare the effects of various concentrations of T on nitric oxide (NO)‐dependent and nitric oxide‐independent relaxation in organ bath studies and elucidate its mode of action, specifically targeting the cavernous NO/cyclic guanosine monophosphate (cGMP) pathway. Materials and methods: Human corpus cavernosum (HCC) samples were obtained from men undergoing penile prosthesis implantation (n = 9). After phenylephrine (Phe) precontraction, the effects of various relaxant drugs of HCC strips were performed using organ bath at low (150 ng/dL), eugonadal (400 ng/dL), and hypergonadal (600 ng/dL) T concentrations. The penile tissue measurements of endothelial nitric oxide synthase (eNOS), neuronal (n)NOS, and phosphodiesterase type 5 (PDE5) were evaluated via immunostaining, Western blot, cGMP and nitrite/nitrate (NOx) assays. Results: Relaxation responses to ACh and EFS in isolated HCC strips were significantly increased at all T levels compared with untreated tissues. The sildenafil‐induced relaxant response was significantly increased at both eugonadal and hypergonadal T levels. Normal and high levels of T are accompanied by increased eNOS, nNOS, cGMP, and NOx levels, along with reduced PDE5 protein expression. Conclusion: This study reveals an important role of short‐term and modulatory effects of different concentrations of T in HCC. T positively regulates functional activities, inhibition of PDE5 expression, and formation of cGMP and NOx in HCC. These results demonstrate that T indirectly contributes to HCC relaxation via downstream effects on nNOS, eNOS, and cGMP and by inhibiting PDE5. This action provides a rationale for normalizing T levels in hypogonadal men with ED, especially when PDE5 inhibitors are ineffective. T replacement therapy may improve erectile function by modulating endothelial function in hypogonadal men.